Association between cellular HIV-1 DNA level and mortality in HIV-1 infected African adults starting ART with high CD4 counts - Jean Baptiste N'takpe (EBioMedicine, 2020)
Background: High HIV-1 DNA levels in peripheral blood mononuclear cells (PBMC) were associated with a higher risk of severe morbidity and a faster decline in CD4 count in ART-naive patients. We report the association between HIV-1 DNA and mortality in HIV-infected adults in a trial of early ART in West Africa. Methods: In the Temprano trial, HIV-infected adults were randomly assigned to start ART immediately or defer ART. After trial termination, HIV-1 DNA was measured in whole blood samples frozen at baseline. We analyzed the association between baseline PBMC HIV-1 DNA and long-term mortality. Findings: 2019 patients were followed for 9253 patient-years (median 4.9 years). At baseline, the median CD4 count was 462/mm3 [IQR 368–571], the median plasma HIV-1 RNA 4.7 log10 copies/ml [IQR 4.0–5.2], and the median HIV-1 DNA 2.9 log10 copies/million PBMC [IQR 2.5–3.3]. During follow-up, 86 participants died. In univariate analysis, the hazard ratio [HR] of death was 2.67 (95% CI, 1.68–4.22) for patients with HIV-1 DNA ≥3 log10 copies/million PBMC vs. others, and 2.10 (95% CI, 1.38–3.21) for patients with HIV-1 RNA ≥5 log10 copies/ml vs. others. In multivariate Cox regression analysis, HIV-1 DNA levels ≥3 log10 copies/million PBMC were strongly associated mortality (adjusted HR = 2.09, 95% CI 1.24–3.52, p= 0.005) while the association between baseline plasma HIV-1 RNA and mortality was not significant. Interpretation: In these African adults who started ART with high CD4 counts, HIV-1 DNA was a strong independent predictor of death. The HIV reservoir still plays a prognostic role in the early ART era. Funding: This trial was supported by the French National Agency for AIDS and viral hepatitis research (ANRS, Paris, France; Grants ANRS 12136, 12224 and 12253)